English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

f(x) = ax^n

f'(x) = (an)x^(n - 1)
f''(x) = (an(n - 1))x^((n - 1) - 1) = an(n - 1)x^(n - 2)
f'''(x) = an((n - 1)(n - 2))x^(n - 3)

so

nth derivative = a(n!)x^(n - (nth derivative))

in otherwords

f(x) = x^(1/2)

f'(x) = (1/2)x^((1/2) - 1) = (1/2)x^(-1/2)
f''(x) = (-1/4)x^((-1/2) - 1) = (-1/4)x^(-3/2)
f'''(x) = (3/8)x^(-5/2)
f''''(x) = (-15/16)x^(-7/2)

the single "n" value is what your value is being raised by
the nth derivative is just the nth derivative
"a" stands for the coefficient.

2006-10-26 16:42:24 · answer #1 · answered by Sherman81 6 · 0 0

nth equals= (1/2)^n * (x)^(1/2-n)

2006-10-26 23:26:17 · answer #2 · answered by Ravi 3 · 1 0

fedest.com, questions and answers